Evaluation of Nutritive Values of Different Diabetic Diet Chart Using in BIRDEM Hospital - Bethe, Rubina Akther; Ahmed, Nur; Ali, Sha Md Keramat; Ali, Liaquat (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.99-104